Long-term impacts of tropical cyclones and fluvial floods on economic growth – Empirical evidence on transmission channels at different levels of development. (August 2021) - Krichene, H.; Geiger, T.; Frieler, K.; Willner, S.N.; Sauer, I.; Otto, C.
Highlights: Tropical cyclones and fluvial floods have significant negative impacts on economic growth in the long run. Development cannot protect against economic growth losses from tropical cyclones. Development can prevent economic growth losses from fluvial floods. Rising household consumption and government expenditure are the main growth-loss mitigating channels. Rising investment is the main growth-loss amplifying channel. Abstract: While the short-term economic impacts of extreme weather events are well documented, little is known about their impacts and transmission channels on economic growth in the long run. Using panel data regressions and national shares of people exposed to tropical cyclones and fluvial floods as exogenous predictors, we find output growth losses from severe tropical cyclones and fluvial floods to accumulate to −6.5% and −5.0% over 15 years, respectively. We further observe a strongly non-linear increase of these losses with disaster intensity. To understand how the observed impacts depend on the countries' development level, we implement a country-specific regression framework. While we find evidence that higher development can prevent economic growth losses from fluvial floods, this is not the case for tropical cyclones. Further, we systematically study the economic and non-economic transmission channels through which these events impact on economic growth in the long run. We find that rising household consumption and government expenditure are the main growth-loss mitigating channels, whereas rising investment is the main growth-loss amplifying channel in the period 1971–2010.